2016
DOI: 10.1002/prep.201500309
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Fast Continuous‐Flow Photo Degradation of Organic Peroxide Explosives for Their Efficient Conversion into Hydrogen Peroxide and Possible Application

Abstract: Fast, quantitative, and efficient direct photo degradation of organic peroxide explosives (HMTD, MEKP, TATP) using characteristic continuous‐flow UV radiation was investigated in aqueous solutions and achieved in less than 30 s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…21,37 Since 2011, the TNT based explosives in artillery shells of US Army were gradually being replaced by IMX-101 which is a mixture of DNAN, NTO and nitroguanidine (NQ). 38 Recently, Mahbub et al 39 reported another type of explosive known as organic peroxide explosives (OPEs) that manifested efficient photo degradation phenomenon despite having very low molar absorptivity coefficients. As opposed to cyclic nitramines and nitroaromatic explosives, the OPEs are extremely unstable and very sensitive to temperature, shock and friction.…”
Section: Photo Degradation Of Explosivesmentioning
confidence: 99%
“…21,37 Since 2011, the TNT based explosives in artillery shells of US Army were gradually being replaced by IMX-101 which is a mixture of DNAN, NTO and nitroguanidine (NQ). 38 Recently, Mahbub et al 39 reported another type of explosive known as organic peroxide explosives (OPEs) that manifested efficient photo degradation phenomenon despite having very low molar absorptivity coefficients. As opposed to cyclic nitramines and nitroaromatic explosives, the OPEs are extremely unstable and very sensitive to temperature, shock and friction.…”
Section: Photo Degradation Of Explosivesmentioning
confidence: 99%
“…H 2 O 2 is also a precursor and a decomposition product of organic peroxides [7], involved in terrorist activities. Hence, detection and quantification of H 2 O 2 is a major concern for safety applications.…”
Section: Introductionmentioning
confidence: 99%
“…nitric, sulfuric or hydrochloric acids), acetone, and hydrogen peroxide (H2O2), are easily accessible. This along with their rapid and simple synthesis has prompted exploitation of OPEs in several public incidences [2]. OPEs are often chosen for such activities because HMTD and TATP achieve near military-grade detonation velocity, calculated as 60% and 88% of the velocity of 2,4,6-trinitro toluene, respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional detection of OPEs has included electrochemical [5,6], acid-hydrolysis [7], photolysis [2] , and reverse phase high performance liquid chromatography-Fourier transform infrared (RP HPLC-FTIR) [8]. Additionally, surface-assisted laser desorption/ionization-time of flight-mass spectrometry (SALDI-TOF-MS) and direct analysis in real time (DART-MS) were employed in analyzing liquid OPE samples spread on ceramic tiles [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation